Change Management Strategy in Islamic Organizations - Dhiya Rahmi Fauza; Ahmad Arif Rahman (Journal of Islamic Economic Scholar, 2021)
Change management is a process of managing change in order to make the best use of it by applying the knowledge, strategies, tools, and resources needed to achieve certain goals. Change management is aimed at providing the business solutions needed successfully in an organized manner and with methods through managing the impact of change on the people involved in it. The purpose of this study is to determine the change management strategies and the causes of making changes so that the changes can be utilized as well as possible. This study uses a positive post approach with the method of collecting literature study data (literature review) of several previous journals that contain research data on change management in English and Indonesian. In this study discusses the strategies and causes of managing change in organizations.